A DISCUSSION ON TWO MODELS OF POLİTİCS OF RECOGNITION: THE STATUS MODEL VS. IDENTITY MODEL - DUMLU, Hediye (Atlas Journal, 2022)
In this study, we will discuss two models of the politics of recognition, the identity model and the status model. The historical roots of the identity model of the politics of recognition go back to the Hegelian philosophy. This model responds to the claims for recognition of individuals who are members of groups based on ethnicity, religion, race, gender and sexual orientation which came to the fore in Western democracies in the last quarter of the twentieth century, especially in the 1980s and 1990s. The identity model undertakes the task of discussing the need for a new justice paradigm, which focuses on the claims for recognition that emerge as new claims for justice, against the justice paradigm that includes claims for an egalitarian redistribution of social resources. However, although it undertakes this important task, it gradually ceases to be a suitable discussion ground due to the problems it contains. The first of these problems is the problem of identity reification, which is based on the assumption that group identity is pre-given, unchanging, and homogeneous, and therefore tends to both mask unequal relations within the group and lead to unequal relations between groups. The second is the displacement problem, which occurs when claims for recognition replace claims for redistribution and the scope of justice is reconceptualized to exclude claims for redistribution. The status model, developed as an alternative to the identity model, neither endorses the recognition of a pre-given, absolute and homogeneous group identity, nor the shift in the center of politics, or the replacement of claims for recognition with claims for redistribution. The status model redefines recognition and misrecognition on the one hand to avoid the problems inherent in the identity model. On the other hand, it undertakes the task of discussing the need for multidimensional justice, which does not neglect the dimension of redistribution as well as the recognition of justice. In this study, we will argue that the status model, which undertakes these challenging tasks, can provide a suitable discussion ground as an alternative to the identity model.